Innovative Strategies for the Management of a Massive Neonatal Rhabdomyoma - Prabhu, N.; Osifodunrin, N.; Murphy, D.; Butler, S.; Hunter, L. E. (Journal of Pediatric Intensive Care, 2018)
Rhabdomyomas are histologically benign tumors known to be associated with tuberous sclerosis. The natural history predicts the majority of tumors to be asymptomatic and regress within the first year of life. We describe a neonate presenting on day 1 of life with cardiovascular collapse secondary to a massive rhabdomyoma. Surgical resection was excluded due to the extensive nature of the lesion and oral sirolimus, a mammalian target of rapamycin inhibitor, was commenced to promote tumor regression. The patient developed intractable arrhythmias requiring extracorporeal life support during therapy.
Keywords: rhabdomyoma; extracorporeal life support; mTOR inhibitors